Understanding the Sustainability of Private Development Initiatives: What Kind of Difference Do They Make?. Issue 2 (4th May 2017) - Kinsbergen, Sara; Schulpen, Lau; Ruben, Ruerd
Abstract: In the Netherlands, there is a large group of small-scale, voluntary development organisations, referred to as Private Development Initiatives (PDIs). By classifying PDI interventions based on their potential sustainability, we aim to enhance our understanding of PDIs as alternative development actors and to get insight into the diversity within this group. We rely on detailed data of 49 Dutch PDIs active in Kenya and Indonesia. The classification is based on a combined analysis of both the intervention type ('what' they do) and the intervention manner ('how' they work) of PDI activities. This results in a typology that outlines the potential sustainability of PDI intervention strategies. We find that diversity regarding the potential sustainability of PDI interventions is large. Whereas several organisational characteristics influence the choice of the intervention strategy (e.g. independence local partner, budget), intrinsic drivers such as motivation and the personal or professional background of PDI members tend to be of great influence for the potential sustainability of the intervention strategies adopted by the PDIs.